PRELIMINARY ANALYSIS ON THE SUCCESS OF COMMUNITY-BASED COMMUNITY ROAD PROGRAM RELATED TO COMMUNITY CHARACTERISTICS, IN PASURUAN CITY - Hitapriya Suprayitno; Ayu Rahmaniyah; Eko Budi Santosa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
As a developing country, Indonesia still has a lot of urban slum areas. Ministry of Public Works and Public Housing create the KOTAKU program, City without Slum. To realize the KOTAKU objective, two projects were conducted the NSUP and the NUSP. Pasuruan City was given the NUSP-2 project, in 2016, covered 11 slum areas, dealt with community road, community sanitation, and community water supply. The success of the community road program had been evaluated. The program was relatively unsuccessful in a coastal area dominated by fisherman settlement. In the next to the coastal area dominated by supporting fishermen supporting an activity, the program was relatively fairly successful. While in urban slum areas dominated by middle-income families, the program was successful.